Effect of food on H2-receptor blockade in normal subjects and duodenal ulcer patients. Issue 2 (February 1990) - Merki, H S; Halter, F; Wilder-Smith, C; Allemann, P; Witzel, L; Kempf, M; Roehmel, J; Walt, R P
Abstract : Two separate studies of 24 hour intragastric acidity were carried out in normal volunteers and duodenal ulcer patients to define the interaction of food and the antisecretory effects of H2-receptor blockers. Both investigations were double blind randomised comparisons using ranitidine 300 mg with either different meal times or ad libitum snacks after an evening meal. Meals taken after drug administration nearly abolished measurable antisectory effects. Median 24 hour pH was 1.3 on placebo, 2.6 when ranitidine was administered after the evening meal and 1.9 when administered before the evening meal. Snacks taken after evening dosing with ranitidine also significantly decreased pharmacodynamic efficacy. During placebo, median night-time pH was 1.3 without snacks and 1.4 with snacks. pH rose to 5.9 during ranitidine treatment when snacks were forbidden but was only 3.1 when snacks were allowed. These findings could be of therapeutic importance and should rationalise dietary advise to patients receiving H2 blockers. The timing of drug administration can be adjusted according to individual life styles.